Academic psychological counseling Between theoretical concepts and applied approaches - Fatima BENLARBI; Ramdan AMOUMEN (Social Sciences Journal, 2021)
The study aims to introduce academic psychological counseling at the university by presenting some models and applications of academic counseling in some universities between theoretical concepts and applied approaches, where academic counseling is a directive process to help the student to know Its potential and optimize it, and this service is considered a quality standard Higher education in the university's, and the latter seeks to pay attention to providing a high level of academic psychological counseling to its students, and to raise the quality of higher education and the quality of its outputs.